2023
DOI: 10.20473/jipk.v15i1.36673
|View full text |Cite
|
Sign up to set email alerts
|

Species Composition and Growth Pattern of a Multi-Species Grouper in Kwandang Bay, Sulawesi Sea, Indonesia

Abstract: Highlight Research There are 26 species identified to be originated from the bay, which the highest diversity in Indonesia Six species found in Kwandang Bay is showing trends of decreasing populations and two species vulnerable based on IUCN conservation list Growth model and Fulton condition factor determined for 14 species indicates that they live in a good state of well beings in the bay The models and condition factors also reflect the adequate food resources required for grouper growth which makes Kwanda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Sampling was conducted twice a month (24 times). Samples of the Variola genus (n = 903) comprised whiteedged lyretail V. albimarginata (n = 529) and the yellowedged lyretail V. louti (n = 374) (Figure 2), both of which are commonly caught in Kwandang Bay (Achmad et al 2023a) and globally assessed as least concern (Nair et al 2018;Sadovy et al 2018). The species of each Variola specimen was determined with reference to the FAO guide to groupers of the world (Heemstra and Randall 1993) and other references (ADB 2017; Michailidis et al 2020).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sampling was conducted twice a month (24 times). Samples of the Variola genus (n = 903) comprised whiteedged lyretail V. albimarginata (n = 529) and the yellowedged lyretail V. louti (n = 374) (Figure 2), both of which are commonly caught in Kwandang Bay (Achmad et al 2023a) and globally assessed as least concern (Nair et al 2018;Sadovy et al 2018). The species of each Variola specimen was determined with reference to the FAO guide to groupers of the world (Heemstra and Randall 1993) and other references (ADB 2017; Michailidis et al 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Kwandang Bay on the Sulawesi Sea (north) coast of Gorontalo Province is one of many Indonesian grouper fishing grounds (Achmad et al 2020;Achmad et al 2021). At least 26 groupers are caught in and traded from Kwandang Bay (Achmad et al 2023a), including two assessed as vulnerable (VU), two as data deficient (DD), and 24 as least concern (LC) in the International Union for Conservation of Nature (IUCN) Red List (IUCN 2022;Achmad et al 2023a). At least two of the groupers classified as LC globally, Epinephelus coioides Hamilton, 1822 (Amorim et al 2018b) and Plectropomus leopardus Lacepède, 1802 (Choat and Samoilys 2018), are overexploited in Kwandang Bay (Achmad et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…According to Yonvitner et al (2021) and Achmad et al (2023), fish growth is an important indicator for assessing the potential for recruitment and recovery of fish population biomass. Based on the von Bertalanffy analysis model in Figure 5, it is found that the growth of an asymptotic length (L∞) for males is 16.094 cm and females L∞ is 15.045 cm.…”
Section: Growth Parametersmentioning
confidence: 99%
“…The lack of data on the structure of grouper stocks in the Tomini Bay and Sulawesi Sea areas under the jurisdiction of Gorontalo Province is an obstacle to designing sustainable management strategies for these ecologically and economically important fishes. Groupers found in Gorontalo waters comprise at least 26 species belonging to 8 genera (Achmad et al 2023). Groupers of the genus Variola are valuable fisheries commodities in this area.…”
Section: Introductionmentioning
confidence: 99%
“…Groupers of the genus Variola are valuable fisheries commodities in this area. Like other groupers, they are also of conservation concern, as there are signs of grouper overfishing in the waters of Gorontalo Province, including the white-edged lyretail Variola albimarginata and the yellow-edged lyretail V. louti (Achmad et al 2023). Therefore, there is a need to examine the population structure of Variola spp.…”
Section: Introductionmentioning
confidence: 99%